2021
DOI: 10.14504/ajr.8.s2.17
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Tea Natural Dye and its Dyeing Properties on Cotton Fabrics

Abstract: Natural dyestuffs are evaluated as green sources to color the fabric in the textile industry. In this study, tea natural dye extracted from Longjing tea was applied to dye cotton fabrics by different dyeing processes. The extraction process was investigated thoroughly according to orthogonal experiments to obtain the optimum results. The acid-base stability, storage stability, heat-resistance, and other properties of Longjing tea natural dye were studied. The rubbing fastness, washing fastness and color differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Dyes or colorants obtained from animal or vegetable matter without any chemical processing regarded as an ecological and sustainable but these have few draw backs such as, low colorfastness and non-availability of standard shade cards [ 4 , 5 ]. An inorganic process was used to extract tea dye from Longjing tea leaves, and after a variety of dying techniques was examined on cotton fabrics, it was discovered that tea dye has a significant potential market and may be used as a commercial natural dye [ 6 ].A study on the application of natural colorants derived from tea leaves for cotton fabric dyeing was conducted on Giza 86 Egyptian cotton fabric. The findings shown that tea leaves may be used as a dye to color fabrics, and that various chemical and natural mordants can be utilized to achieve varied color tones [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dyes or colorants obtained from animal or vegetable matter without any chemical processing regarded as an ecological and sustainable but these have few draw backs such as, low colorfastness and non-availability of standard shade cards [ 4 , 5 ]. An inorganic process was used to extract tea dye from Longjing tea leaves, and after a variety of dying techniques was examined on cotton fabrics, it was discovered that tea dye has a significant potential market and may be used as a commercial natural dye [ 6 ].A study on the application of natural colorants derived from tea leaves for cotton fabric dyeing was conducted on Giza 86 Egyptian cotton fabric. The findings shown that tea leaves may be used as a dye to color fabrics, and that various chemical and natural mordants can be utilized to achieve varied color tones [ 7 ].…”
Section: Introductionmentioning
confidence: 99%